PEMBERDAYAAN PEMUDA MELALUI PENYULUHAN GAYA HIDUP BERKELANJUTAN SEBAGAI UPAYA PELESTARIAN LINGKUNGAN DI KAWASAN TANJUNG DAPURA - Abdul Rahman; Parham Taufik; Andi Supratman; Jumadi; Nurlela (CV. Kalimasada Group, 2026)
This community service activity aims to enhance the awareness and capacity of youth in implementing sustainable lifestyles in the Tanjung Dapura area, Makassar. The main problems faced by the community include low levels of waste management practices, high dependence on single-use plastics, and limited environmental literacy. The implementation method applied a participatory approach through several stages, including initial observation, interactive counseling, group discussions, and simulations of sustainable lifestyle practices. The results indicate a significant improvement in participants’ understanding and awareness of environmental sustainability, reflected in changes in perspectives and the emergence of commitments to reduce plastic use and manage waste independently. Furthermore, participants demonstrated strong enthusiasm to act as agents of change within their communities. Therefore, this activity is considered effective in empowering youth as key drivers in promoting environmental sustainability in coastal areas.